The Role of Islamic Education in Moral Decadence in Children: A Study of Al-Mishbah's Interpretation of QS. Luqman: 12-19 - Cahyanti, Elysa Februana Nur; Shohib, Muhammad Wildan (Universitas Muhammadiyah Surakarta, 2025)
Moral decadence among children today has become a serious problem in line with the rapid development of science and technology, which has weakened the character building of the younger generation. This phenomenon is marked by an increase in deviant behavior, such as gang fights, promiscuity, and a decline in respect for parents. This condition shows a low level of understanding and practice of moral values. Therefore, solutions based on Islamic values are needed to overcome the moral crisis among children. This study aims to examine the concept of moral decadence, explore the theory of Islamic education according to M. Quraish Shihab, and analyze the relevance of Islamic education in overcoming moral decadence among children. This study uses a qualitative approach with a library research method, with the main source being Tafsir Al-Mishbah by M. Quraish Shihab. The results show that moral decadence is a decline related to behavior, personality, and character of individuals. Islamic education is understood as an educational process that is carried out consciously and deliberately based on Islamic law to achieve certain goals. According to M. Quraish Shihab, the main objective of Islamic education is to shape individuals so that they are able to carry out their roles as servants of Allah and caliphs on earth. Islamic education has strong relevance in overcoming moral decadence in children through instilling values of faith and gratitude, cultivating attitudes of love and respect for parents, encouraging good deeds, performing acts of worship, and forming noble character based on patience and sincerity.